Life and fate - Grossman, Vasiliĭ (Everyman's library (Alfred A. Knopf, Inc.), 2022)
"Suppressed by the KGB and years later smuggled out of the Soviet Union to be published, Vasily Grossman's novel is an unsparing story of ordinary Russians tragically caught between the fascism of the invading Nazis and the oppression of their own Soviet government. The sprawling plot follows the travails of the extended family of Viktor Shtrum along the vast eastern front of the war. Shtrum is a brilliant nuclear physicist who faces rising anti-Semitism in Moscow while his relatives navigate the threat of camps and prisons on both the Soviet and the Nazi sides. Grossman's extensive wartime reporting, combined with his Tolstoyan narrative skills, allow him to portray with unprecedented detail and authenticity the human cost of the struggle between two freedom-denying powers. In vividly rendered scenes that range from the dramatic battle of Stalingrad to the remote Siberian gulag, and encompassing characters ranging from a grieving mother to a woman in love and from a six-year-old boy on the way to a gas chamber to Stalin and Hitler, Grossman's masterpiece is a profound and moving reckoning with the darkness of the twentieth century and a testament to the stubborn persistence of kindness and hope."--Publisher.